Long-term follow-up of children with acute promyelocytic leukemia treated with Beijing Children's Hospital APL 2005 protocol (BCH-APL 2005). (3rd October 2019) - Zhang, Yuanyuan; Wang, Linya; Zhang, Ruidong; Qi, Peijing; Xie, Jing; Shi, Huiwen; Lin, Wei; Wu, Ying; Yu, Jiaole; Fan, Jia; Feng, Guoshuang; Zheng, Huyong; et al.
Abstract: We studied the outcomes of children with APL treated by the Beijing Children's Hospital's (BCH) acute promyelocytic leukemia (APL) 2005 protocol (BCH-APL2005). The clinical data of 77 patients enrolled from January 2005 to June 2015 were analyzed retrospectively. The hematologic complete remission (CR) rate and overall survival (OS) rate were evaluated between standard-risk (SR) and high-risk (HR) groups. Prognostic factors and complications were investigated in these two groups. CR in the SR and HR groups was 96.4% (54/56) and 85.7% (18/21), respectively, while the 10-year OS was 94.6% (53/56) and 76.2% (16/21), respectively. The cumulative incidence of early death was 6.5% (5/77), and the SR and HR groups were 1.8% (1/56) and 19.0% (4/21), respectively. Only two patients relapsed, and the relapse rate was 2.6% (2/77). According to Kaplan–Meier analysis, the SR group had a significantly better long-term survival than HR counterparts ( p = .016). Initial leukocyte count was the only prognostic factor ( p = .016) by univariate analysis, while other factors, such as FLT3-ITD and platelet count, had no correlation with prognosis. In addition, early deaths were mainly due to intracranial hemorrhage. Although the combination of all-trans retinoic acid (ATRA) and chemotherapy can improve the outcome of APL patients, the early deaths and anthracycline-related cardiac toxicity were relatively higher in our study. Current efforts focus on reducing or even avoiding chemotherapy in APL children and rest on the frontline regimen of intravenous arsenic trioxide or oral realgar-indigo naturalis formula plus ATRA, which is the direction for APL treatment.